An experimental investigation of a microturbine simulated rotor supported on multileaf gas foil bearings with backing bump foils. (September 2018) - Zhang, Bo; Qi, Shemiao; Feng, Sheng; Geng, Haipeng; Sun, Yanhua; Yu, Lie
Two multileaf gas foil journal bearings with backing bump foils and one set of gas foil thrust bearings were designed, fabricated, and used in a 100 kW class microturbine simulated rotor system to ensure stability of the system. Meanwhile, a preliminary test rig had been built to verify the simulated system stability. The rotor synchronous and subsynchronous responses were well controlled by using of the gas foil bearings. It is on the multileaf gas foil bearings with backing bump foils that the test was conducted and verified for the first time in open literatures. The success in the experiments shows that the design and fabrication of the rotor and the gas foil bearings can provide a useful guide to the development of the advanced high speed rotating machinery.